Detecção de zona híbrida entre Cattleya coccinea e C. brevipedunculata (Orchidaceae) no Parque Estadual do Ibitipoca, Minas Gerais, utilizando microssatélites e análise morfométrica - Barbara Simoes Santos Leal (2013)
Although the expression of morphological traits in hybrid is unpredictable, often resulting in a mosaic of parental, intermediate, and new characters, many natural hybrids of Orchidaceae have been reported only through the observation of intermediate phenotypes to its putative parental. Molecular markers have been shown to be a good tool to test such morphological hypotheses and to characterize the architecture of natural hybrid zones in plants, including in Orchidaceae. In this study, we used multivariate morphometric analyses of 24 floral and vegetative characters and molecular genetic analysis, based in seven microsatellite loci, to investigate a supposed hybrid zone between Cattleya coccinea Lindl. and C. brevipedunculata (Cogn.) Van den Berg (Epidendreae: Laeliinae), located at Parque Estadual do Ibitipoca (PEI), Minas Gerais state, Brazil. Both species are mainly distinguished by leaf and pseudobulb size and form and peduncle length, and also by geographical distribution. Morphometric analyses support differences between C. coccinea and C. brevipedunculata and indicate a continuum of variation at PEI, with the extremes of this continuum overlapping the morphology of allopatric populations used as reference. The variability and genetic structure data, however, do not confirm the hypothesis of hybridization nor introgression at PEI, and accumulated evidences from bayesian analysis of genetic structure, cluster analysis and distribution of allelic frequencies indicate that it is a pure population of C. brevipedunculata. Unlike other known populations of this species, where individuals occur in open sunny sites, the individuals of PEIs population also occur in the woods, under shaded conditions. The morphological variation observed may thus be related to phenotypic plasticity of vegetative traits in response to changes of light incidence, as indicated by significant differences in leaf and pseudobulb characters between individuals located at rock outcrops and woods. These results demonstrate the unreliability of morphology for detecting natural hybrids and the potential of vegetative characters as a confounding factor in distinguishing closely related taxa.